SARAF and Orai1 Contribute to Endothelial Cell Activation and Angiogenesis - Galeano-Otero, Isabel; Del Toro, Raquel; Khatib, Abdel-Majid; Rosado, Juan Antonio; Ordóñez-Fernández, Antonio; Smani, Tarik (Frontiers in Cell and Developmental Biology, 2021)
Angiogenesis is a multistep process that controls endothelial cells (ECs) functioning to form new blood vessels from pre-existing vascular beds. This process is tightly regulated by pro-angiogenic factors, such as vascular endothelial growth factor (VEGF), which promote signaling pathways involving the increase in the intracellular Ca2+ concentration ([Ca2+]i). Recent evidences suggest that Store-Operated Calcium Entry (SOCE) might play a role in angiogenesis. However, little is known regarding the role of SARAF, SOCE-associated regulatory factor, and Orai1, the pore forming subunit of the Store Operated Calcium Channel (SOCC), in angiogenesis. Here, we show that SOCE inhibition with GSK-7975A blocks aorta sprouting, as well as Human Umbilical Vein Endothelial Cells (HUVECs) tube formation and migration. The intraperitoneal injection of GSK-7975A also delays the development of retinal vasculature assessed at postnatal day 6 in mice, since it reduces vessels length, the number of junctions, while it increases lacunarity. Moreover, we find that SARAF and Orai1 are involved in VEGF-mediated [Ca2+]i increase, and their knockdown using siRNA impairs HUVECs tube formation, proliferation and migration. Finally, immunostaining and in situ proximity ligation assays indicate that SARAF likely interacts with Orai1 in HUVECs. Therefore, these findings show for the first time a functional interaction between SARAF and Orai1 in ECs and highlight their essential role in different steps of angiogenesis process.